2018
DOI: 10.1007/s00300-018-2272-y
|View full text |Cite
|
Sign up to set email alerts
|

Ascidian distribution provides new insights to help define the biogeographic provinces in the South American Region

Abstract: The validity and size of the biogeographic Magellan Province of marine organisms have been the focus of discussion of many authors. The distribution of fish and other organisms has revealed a lack of homogeneity in the area, which has also been interpreted as comprising four different Provinces: Southern Chile (SCH), Tierra del Fuego (TDF), Southern Argentina (SAR), and the Malvinas/Falkland Islands (MAI). For the first time, we assess the ascidian fauna of this region to determine if the distribution of benth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Ascidian diversity studies in this region have been mainly performed in the Patagonian shelf, South Argentina (e.g. Van Name 1945;Diehl 1977;Lagger & Tatián 2013;Taverna et al 2018), and Brazil (e.g. Rocha & Costa 2005;Bonnet & Rocha 2011;Moreno et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ascidian diversity studies in this region have been mainly performed in the Patagonian shelf, South Argentina (e.g. Van Name 1945;Diehl 1977;Lagger & Tatián 2013;Taverna et al 2018), and Brazil (e.g. Rocha & Costa 2005;Bonnet & Rocha 2011;Moreno et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the benthic communities found on the Burdwood Bank slope are similar to those described for northern sectors on the Argentinean slope (see Portela et al, , ; Schejter et al, ), which evidences a continuous habitat in which the Malvinas (Falkland) Current flows. Some important results obtained from the study of the samples taken during the Argentinean research cruises between 2013 and 2018 are the inventories of ascidians (Taverna et al, ), Asteroidea (Fraysse, Calcagno, & Pérez, ), brachiopods (Gordillo, Bayer, de Aranzamendi, Taverna, & Morán, ), molluscs (Di Luca & Zelaya, ), and polychaetes (Bremec et al, ), and the distribution and reproduction of some fishes have been also reported by García Alonso, Brown, Martín, Pájaro, and Capitanio (). Several new species have also been discovered in this area (Schejter, Bertolino, & Calcinai, ; Güller & Zelaya, ; Urcola & Zelaya, ; López Gappa, Liuzzi, & Zelaya, ), and many more are undergoing the description process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exhaustive species inventories, descriptions of new species, new records of distribution, and studies on reproductive biology and biogeography have been recently published on the fauna from Burdwood Bank (Güller and Zelaya 2017; Penchaszadeh et al 2017Penchaszadeh et al , 2019Schejter et al 2017a;Fraysse et al 2018Fraysse et al , 2020García Alonso et al 2018;López Gappa et al 2018;Taverna et al 2018;Urcola and Zelaya 2018;Bremec et al 2019;Di Luca and Zelaya 2019;Gordillo et al 2019;Teso and Penchaszadeh 2019;Pérez-Barros et al 2020;Roccatagliata 2020;among others).…”
Section: Introductionmentioning
confidence: 99%